Differential display of flower bud mRNA of genic male sterility (GMS) AB line in Chinese cabbage-pak-choi and analysis of differential cDNA fragments - CAO Jia-shu; YE Wan-zhi; ZHANG Ming; ZENG Guang-wen (浙江大学学报. 农业与生命科学版, 2001)
The difference was compared by mRNA differential display technology in Chinese cabbage-pak-choi (Brassica campestris ssp. chinensis Makino var. communis Tsen et Lee) flower bud among genic male sterility (GMS) line (A line) and maintainer line (B line). 18 differential fragments have been obtained in total of 120 selective amplifications. A differential fragment named as B0302-4 was confirmed by Northern hybridization out of 6 cDNA differential fragments tested. B0302-4 was shared by the maintainer line the expression of B0302-4 was restricted in the GMS line, and B0302 4 expressed specially in flower bud. Fragment B0302-4 is composed of 463 base pair. The result of Gen-Bank BLAST showed that it has 84.3% nucleotide similarity to the CYP86C4 gene encoding cytochrome P450 from Arubidopsis.